PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE CONTINUOUS REVIEW SYSTEM DAN METODE PERAMALAN PADA PT XYZ - Danang Prihandoko; Nexia Tanadjaya; Christine Chendrawaty (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to determine the optimal number of orders, estimated costs, reorder points, and safety stock. This study uses quantitative methods and aims to provide inventory control proposals using Continuous Review System analysis and Forecasting with QM software for windows. So as to obtain optimal order results A3 + Glossy 8060 pack stickers with a cost of Rp. 545,508,208.43. A3 + Matte stickers 3,238 pack with a fee of Rp 237,554,470.91. A3 + Transprent 4,181 pack stickers at a cost of Rp. 294,737,067.25. Furthermore, a Reorder Point point of 1,520 packs for Glossy, 687 packs for Matte, and 732 packs for Transparent and Safety Stock Level for Glossy of 189 packs was obtained. Matte of 117 packs, Transparent of 97 packs. Based on the results of these calculations it can be concluded that using the Continuous Review System method can control inventory and estimate the cost to be incurred more effectively and efficiently by the company. (NT, CC, JK)